McGill School of Religious Studies Bachelor of Theology Survey - Rosini, Amanda; Neba, Prudence (Journal of the Council for Research on Religion)

(untitled) (Council for Research on Religion, 2023)
This paper offers a brief analysis of a survey created with the intent of better understanding the student experience of those enrolled in McGill University’s Bachelor of Theology. The questions were crafted with the objective of understanding how certain demographic features – education, age, ethnicity, and origin of province or country – have affected the experience of students in the Bachelor of Theology program during their first semester. The paper reviews the survey data with the aim of offering some tangible ways to better meet the changing needs of current and future students in McGill’s Bachelor of Theology program.